Origin of hysteresis in current-voltage characteristics of polycrystalline silicon thin-film transistors - Lin, Horng-Chih; Hung, Cheng-Hsiung; Chen, Wei-Chen; Lin, Zer-Ming; Hsu, Hsing-Hui; Hunag, Tiao-Yuang (My University, 2009)
In this work we report the observation and characterization of a hysteresis phenomenon in the transfer characteristics of n-channel polycrystalline silicon (poly-Si) thin-film transistors (TFTs). Such phenomenon is observed in devices with fully depleted channel and not treated with hydrogen-related anneal. The origin of the hysteresis is identified to be related to the electron trapping and detrapping processes associated with the deep-level traps in the grain boundaries of the poly-Si channel.
Keywords: deep levels; defect states; electron traps; elemental semiconductors; grain boundaries; hysteresis; interface states; silicon; thin film transistors